2020
DOI: 10.1080/00918369.2020.1804256
|View full text |Cite
|
Sign up to set email alerts
|

Service Provider Perspectives of Minority Stress among Black, Asian and Minority Ethnic Lesbian, Gay and Bisexual People in the UK

Abstract: Mental health inequalities among Black, Asian and Minority Ethnic (BAME) people from lesbian, gay and bisexual (LGB) communities persist and remain under-researched. This study is the first in the UK to explore, from the perspective of service providers, minority stress experienced by BAME LGB people. Twenty-three participants were interviewed and data were analysed using qualitative thematic analysis. Minority stress theory was utilised to inform the analysis, yielding the following themes: (1) Stress induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 82 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…The notion that specific groups of individuals may experience stress as a function of their specific minority status in society is one that has been increasingly investigated (Meyer, 1995 ). This has been specifically recognised in relation to ethnic minority groups (Rehman et al, 2021 ), and LGBTQIA + populations (Weeks et al, 2021 ), but pressures to fit with specific societal norms and/or conceal aspects of oneself has also been applied to autistic populations (Botha & Frost, 2018 ). It may therefore be important for future research to develop instruments capable of indexing specific aspects of worry and stress experienced by autistic individuals to better understand and address issues that are not shared with the broader community upon which most instruments are normed and validated.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that specific groups of individuals may experience stress as a function of their specific minority status in society is one that has been increasingly investigated (Meyer, 1995 ). This has been specifically recognised in relation to ethnic minority groups (Rehman et al, 2021 ), and LGBTQIA + populations (Weeks et al, 2021 ), but pressures to fit with specific societal norms and/or conceal aspects of oneself has also been applied to autistic populations (Botha & Frost, 2018 ). It may therefore be important for future research to develop instruments capable of indexing specific aspects of worry and stress experienced by autistic individuals to better understand and address issues that are not shared with the broader community upon which most instruments are normed and validated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this expectation around heteronormativity, there is evidence to suggest that non-heterosexuality should be concealed in order to protect their family honor. For instance, Rehman and colleagues [46] conducted a qualitative thematic analysis in the UK to explore the minority stress experienced by Black, Asian, and Minority Ethnic (BAME) LGB individuals. The South Asian community members expressed that they feel the burden of not damaging their family's "izzat" (honor/respect) that leads to shame within the community and increasing the risk of being the targets of gossip and ridicule [46].…”
Section: Internalized Sexual Stigma For Lesbian Gay and Bisexual Asiansmentioning
confidence: 99%
“…For instance, Rehman and colleagues [46] conducted a qualitative thematic analysis in the UK to explore the minority stress experienced by Black, Asian, and Minority Ethnic (BAME) LGB individuals. The South Asian community members expressed that they feel the burden of not damaging their family's "izzat" (honor/respect) that leads to shame within the community and increasing the risk of being the targets of gossip and ridicule [46]. These values of Confucianism and family honor are associated with both ISS, e.g., [35,36,44] and also with guilt and shame, e.g., [45][46][47].…”
Section: Internalized Sexual Stigma For Lesbian Gay and Bisexual Asiansmentioning
confidence: 99%
“…Studies in both the U.K. and the U.S. have indicated that the pressures of managing both a Black and a gay identity can be impactful, particularly to respondent's mental health (Rehman et al, 2020, Wilson et al, 2018. There have also been American studies (Ford, 2015) that look specifically at the experience of Black, gay university students.…”
Section: The Black/gay Dyadmentioning
confidence: 99%
“…This presents something of a paradox, given it is widely accepted that the more identities that can be oppressed the more the exposure to poor mental health outcomes such as is the case for LGBT+ people and described in Meyer's minority stress theory (2003). Rehman et al (2020) provides a study looking into some of the unique mental health challenges that can be faced by Black LGBT+ people and encourages an update of the Minority Stress theory in that it is not enough just to look at the vulnerabilities faced by LGBT+ people, as the theory highlights, but to also make the framework culturally appropriate as well, given the higher levels of stress that Black LGBT+ people suffer as a result of these identity intersections.…”
Section: Emergent Themes and Existing Literaturementioning
confidence: 99%